A systematic review of methods to assess intake of sugar-sweetened beverages among healthy European adults and children: a DEDIPAC (DEterminants of DIet and Physical Activity) study. Issue 4 (21st October 2016) - Riordan, Fiona; Ryan, Kathleen; Perry, Ivan J; Schulze, Matthias B; Andersen, Lene Frost; Geelen, Anouk; van't Veer, Pieter; Eussen, Simone; van Dongen, Martien; Wijckmans-Duysens, Nicole; Harrington, Janas M
Abstract: Objective: Research indicates that intake of sugar-sweetened beverages (SSB) may be associated with negative health consequences. However, differences between assessment methods can affect the comparability of intake data across studies. The current review aimed to identify methods used to assess SSB intake among children and adults in pan-European studies and to inform the development of the DEDIPAC (DEterminants of DIet and Physical Activity) toolbox of methods suitable for use in future European studies. Design: A literature search was conducted using three electronic databases and by hand-searching reference lists. English-language studies of any design which assessed SSB consumption were included in the review. Setting: Studies involving two or more European countries were included in the review. Subjects: Healthy, free-living children and adults. Results: The review identified twenty-three pan-European studies which assessed intake of SSB. The FFQ was the most commonly used ( n 24), followed by the 24 h recall ( n 6) and diet records ( n 1). There were several differences between the identified FFQ, including the definition of SSB used. In total, seven instruments that were tested for validity were selected as potentially suitable to assess SSB intake among adults ( n 1), adolescents ( n 3) and children ( n 3). Conclusions: The current review highlights the need for instruments to use an agreed definition of SSB. Methods that were tested for validity and used in pan-European populations encompassing a range of countries were identified. These methods should be considered for use by future studies focused on evaluating consumption of SSB.